New Perspective on Factors Related to Coalition Success. Issue 6 (November 2015) - Bornstein, Daniel B.; Pate, Russell R.; Beets, Michael W.; Ortaglia, Andrew; Saunders, Ruth P.; Blair, Steven N.
<x xml:space="preserve">Abstract</x> Context: Physical activity (PA) coalitions are a fundamental component of efforts to increase population levels of PA in the United States. Coalitions are often composed of organizational members including government agencies, for-profit corporations, and nonprofit organizations. Very little is known about PA coalitions, their organizational members, and the factors related to their success. Objective: First, this study aimed to describe the characteristics of PA coalitions across the United States. Second, the study aimed to describe the characteristics of organizational members of PA coalitions. Third, the study aimed to investigate the association between organizational membership and coalition success. Design: A cross-sectional design was employed to study individuals from a diverse sample of PA coalitions across the United States. A total of 120 individuals (86% response rate) completed the Member Involvement in Physical Activity Coalitions (MIPAC) survey. The MIPAC included 3 sections: (1) demographic items assessing descriptive characteristics of PA coalitions and their organizational members; (2) 3 subscales for assessing key organizational membership factors (Strategic Alignment, Organizational Alignment, and Providing Input); and (3) 2 subscales for assessing perceived coalition success. Main Outcome Measures: Descriptive statistics characterize PA coalitions and their organizational members. Univariate analyses were employed to investigate associations between key organizational membership factors and perceived coalition success. Results: Statistically significant associations were observed between the key organizational membership factors (Strategic Alignment, Organizational Alignment, and Providing Input) and measures of perceived coalition success. Many PA coalitions lacked organizational members from the settings in which the coalitions strive to make change. Conclusions: Physical activity coalitions and health-based coalitions overall may be more likely to succeed when they can identify ways in which their coalition provides opportunities for strategic alignment, organizational alignment, and providing input to existing and perspective organizational members. In addition, PA coalitions may benefit from engaging more organizational members from the built environment and education sectors.